The birthplace of soccer players of Brazilian national teams in world cups - Verdini de Carvalho, L. A.; Machado, J. F.; Soares de Sousa, A. P.; Fernandes Filho, J. (SportLogia, 2018)
The study has the objective to identify the region where the players from the male Brazilian Soccer National Teams were born and that represented Brazil 1st teams in World Cups. It was analyzed all the players who represented Brazil 1st National Teams in all World Cups organized by Football International Football Association from 1930 to 2014 . The Brazilian soccer register expressive results worldwide regarding winning Cups and providing top players to the soccer market in different countries. The result shows that the distribution it is heterogeneous about the birthplace of the soccer players . The southeast and the south regions concentrate 86,6% of the born place and only two Federative Units. Sao Paulo and Rio de Janeiro have 63,46 % . The professional soccer player origin , still needs deep studies to be oriented regarding potential demands into the formation of the soccer player.